The Values of Systemic Immune-Inflammation Index and Neutrophil–Lymphocyte Ratio in Predicting Biochemical Recurrence in Patients With Localized Prostate Cancer After Radical Prostatectomy - Wang, Shuo; Yang, Xiao; Yu, Ziyi; Du, Peng; Sheng, Xinan; Cao, Yudong; Yan, Xieqiao; Ma, Jinchao; Yang, Yong (Frontiers in Oncology, 2022)
Purpose: To investigate the association between preoperative systemic immune-inflammation index (SII) and neutrophil-lymphocyte ratio (NLR) and oncological outcomes in localized prostate cancer (PCa) patients after radical prostatectomy (RP). Methods: Between January 2014 and December 2019, 291 patients with pathological confirmed localized PCa underwent RP were included into this study. The threshold values of SII and NLR for biochemical recurrence (BCR) were calculated according to receiver operating characteristic (ROC) curve, then the patients were divided into 2 groups by threshold value of SII and NLR. The binary logistic regression model was used to evaluate the association between SII, NLR and pathological outcome. Kaplan-Meier curves, univariable and multivariable COX regression model were used to determine the association between high SII, high NLR and BCR free survival, respectively. Results: The median follow-up time was 48 months (IQR 36-62), 114 (39.18%) patients developed BCR. The threshold values of SII and NLR were 528.54 and 2.62, respectively. Patients in high SII group had higher tPSA, GS, pT stage and BCR rate than patients in low SII group (P=0.004, 0.04, 0.007 and <0.001); and patients in high NLR group had higher tPSA, GS, pT stage and BCR rate than patients in low NLR group (P=0.04, 0.02, 0.006 and <0.001). Regression analysis revealed that high SII was significantly correlated with adverse pathological outcomes of GS (HR, 1.656; 95% CI, 1.00-2.742, P=0.042) and pT stage (HR, 1.478; 95% CI, 0.972-3.64, P=0.028); there was no association between high NLR and pathological events. Kaplan-Meier analysis showed significantly poorer BCR free survival in patients with a high SII or high NLR, P<0.001, <0.001, respectively. By using multivariable COX regression model, high SII (HR, 4.521; 95% CI, 2.262-9.037, P<0.001) and high NLR (HR, 4.787; 95% CI, 2.339-9.798, P<0.001) were both significant predictors of BCR after RP. Conclusion: High SII was significantly related to unfavorable clinicopathological outcomes; high preoperative SII and NLR were related to higher BCR rate in localized PCa after RP, and they were all independent risk factors associated with shorter BCR free survival; these two factors might provide promising and unexpensive methods predicting clinical outcomes in patients with RP.